2006
DOI: 10.14742/ajet.1280
|View full text |Cite
|
Sign up to set email alerts
|

ICT integration in schools: Where are we now and what comes next?

Abstract: The case for more technology in schools is compelling. The leverage for a school based solution is traceable to the Common and Agreed National Goals for Schooling (AEC, 1989), namely that students will develop skills in 'information processing and computing'. Schools have wrestled with this 'integration challenge' since 1989. This paper is a snapshot of the ICT efforts of 18 regional schools as they come to terms with the challenge of ICT integration. Building on the work of Lim et al (2003), and the JISC (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Many authors and teacher educators have explored the introduction and use of information and communication technologies in the school classroom from a variety of international perspectives (Baskin & Williams, 2006;Kangro & Kangro, 2004;Lim et al, 2003;Misra, 2006;Vavouraki, 2004). What is clear from this body of work is that technologies cannot be introduced in an ad hoc or top-down manner.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors and teacher educators have explored the introduction and use of information and communication technologies in the school classroom from a variety of international perspectives (Baskin & Williams, 2006;Kangro & Kangro, 2004;Lim et al, 2003;Misra, 2006;Vavouraki, 2004). What is clear from this body of work is that technologies cannot be introduced in an ad hoc or top-down manner.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the analysis of the factors that affect the integration of ICT in education in countries like Australia (Baskin andWilliams 2006, andHayes 2007), Belgium (Tondeur, Valcke, and van Braak 2008), the Netherlands (Mooji and Smeets 2001), Israel (Nachmias et al 2004, andTubin et al 2003), Malaysia (Cloke and Sharif 2001), the United Kingdom (Kirkman 2000;Tearle 2003Tearle , 2004, and Singapore (Lim 2002, andLim andHang 2003), Rodriguez et al (2012) identified three main settings where inputs are processed: (i) classroom where teaching and/or learning occurs, even though it might not happen within a classroom (e.g., computer lab); (ii) school which is the specific educational institution in which ICT-enhanced teaching and/or learning takes place; and (iii) external setting which considers those processes that are outside of schools (e.g., public policies, monitoring, and assessment). These settings are shown in Table A1.3.…”
Section: G Current Support Logisticsmentioning
confidence: 99%
“…We refer to the role that the structural and organisational variables of the teaching context play in the effect that ICT have on teaching practices, a topic that has been dealt with in much previous research (Ruthven, Hennessy & Deaney, 2005;Baek, Jung & Kim, 2006;Baskin & Williams, 2006;Cartwright & Hammond, 2007;Bate, 2010). In this study we will refer to these structural and organisational variables when describing the video recorded class sessions, but when focusing on the analysis of the direct teaching in classroom practice, this context serves only as an interpretative framework for ICT practices.…”
Section: Research Objectivesmentioning
confidence: 99%